Birokrasi, Akses Informasi, dan Siasat Warga Prekariat di Negara Pascakolonial - Hamdi, Mujtaba (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2020)
The assumption that the state operates fully rational-formal is increasingly difficult to maintain. The state is much better seen not as a single solid and monolithic entity, but as a formation that continues to shape itself through various processes of internal and external power competition, which cannot be separated from kinship factors, social organizational patterns, and, in certain contexts, the history of colonialism. . Market penetration which has recently become increasingly dominant towards various sides of the state and the bureaucracy has added a new dimension and complexity to the relationship between citizens and the state. This paper intends to show the dynamics of these formalities by revealing the nature of power that underlies state formation. On the other hand, this paper will show how precarious citizens move between rationality as well as irrationality, formality and informality, to access the state space which is considered completely rational and increasingly has a market character.